ASPEK HUKUM LABORATORIUM FORENSIK KEIMIGRASIAN: STUDI KASUS PEMERIKSAAN PASPOR PALSU KEBANGSAAN INGGRIS ATAS NAMA ABBAS TAUQEER - Syahrin, Muhammad Alvi (Universitas Borneo Tarakan, 2018)
ABSTRACTIncreased traffic flow of people entering and leaving Indonesia, had causing various level of immigration crimes. Passport fraud as a crime committed by replacing, altering part or all of a passport, or using false information to receive a passport, has become a serious matter now. Currently, almost all the proof of counterfeit passport process is checked in the Immigration Forensic Laboratory at the Immigration Intelligence Directorate. The formulation of the problem studied in this paper is how the role and challenge of Immigration Forensic Laboratory in conducting examination of fake passport on behalf of Abbas Tauqeer. The research method used is normative and empirical legal research. Based on the results of the research can be seen that the Immigration Forensic Laboratory has an important role as the center of examination of fake immigration documents consisting of several technical stages. Forensic analysis of the case found damage to passport biodata pages, different types of letters on passport biography, photos and biodata replaced, passport chips damaged, and unreadable chips in Automatic Document Reader. Then, the challenges faced include the lack of human resources, facilities and infrastructure has not been representative, the absence of Standard Operational Procedure (SOP), and the lack of care of officers in the field.Keywords: Immigration Forensic Laboratory, Counterfeit Passport